DNA metabarcoding of gut contents reveals natural predation by spiders on Xylella fastidiosa vectors in the southwestern Spain agroecosystem - Laura Avivar-Lozano; José M. Molina; Sergio Pérez-Guerrero (Spanish Journal of Agricultural Research)
Aim of study: To elucidate which species and specific guilds of spiders prey on vectors of Xylella fastidiosa from agroecosystems in southwestern Spain using metabarcoding approach.